Determination of lower flammability limits of C-H-O compounds in air and study of initial temperature dependence - Mendiburu, Andrés Z. [UNESP]; de Carvalho, João A. [UNESP]; Coronado, Christian R.; Chumpitaz, German A. (Elsevier, 2016)
The main objective of this study was to develop a method that can be used to estimate the lower flammability limits of C-H-O compounds at standard temperature and pressure. In addition, a study was carried out to develop a method that can be used to determine lower flammability limits at different initial temperatures at 1 atm. Several 374 C-H-O compounds were used to develop the method which determines the lower flammability limits at standard temperature and pressure. This group of compounds was divided into two sets, one for correlation and another for prediction. The correlation set was made up of 273 compounds while the prediction set was made up of 101 compounds. The average absolute relative error was 5.53% for the correlation set, while the squared correlation coefficient was 0.9758; the average absolute error was 5.25% and the squared correlation coefficient was 0.9699 for the prediction set; and the average absolute error was 5.43% and the squared correlation coefficient was 0.9752 for the total set. These parameters show that the method is very accurate. The dependence of the lower flammability limit on the initial temperature was studied for a total set of 26 compounds. It was found that the adiabatic flame temperature at the lower flammability limit cannot always be assumed to be constant. A method that can be used to estimate the LFLs at different initial temperatures was developed; this method had an average absolute relative error of 1.85% and a squared correlation coefficient of 0.9987.
Keywords: C-H-O compounds; Estimation; Lower flammability limits; Temperature dependence